Hubungan Kecanduan Gadget dengan Kecerdasan Emosional pada Remaja - Mulyanti, Aisyah; Dolifah, Dewi; Rahmat, Delli Yuliana (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
In the era of digitalization, teenagers are vulnerable to the influence of technology, where gadgets become one of the main sources of interaction and entertainment. Consequently, gadget addiction can disrupt the emotional development of teenagers, reducing their ability to regulate emotions and interact socially. The aim of this study is to investigate the relationship between gadget addiction and emotional intelligence among teenagers at SMK Informatika Sumedang. This research is a quantitative study of observational analytic type with a cross-sectional approach. Sampling method is conducted through quota sampling technique with 101 respondents. There are two instruments used in this study adapted from previous research: SAS-SV to measure the level of gadget addiction and TEIQ-ASF questionnaire to assess emotional intelligence level. This study employs two-stage analysis, namely univariate analysis to determine frequency distribution and bivariate analysis using Spearman rank correlation test. The results of the study show that 56.4% experience high-level gadget addiction and 43.6% low-level, while 76.2% have moderate emotional intelligence, 19.8% low, and 4% high. The bivariate test results obtained a p-value = 0.000 which means there is a relationship between gadget addiction and emotional intelligence. Furthermore, the correlation coefficient value of rho = 0.375 indicates a positive direction of the relationship. In conclusion, there is a relationship between gadget addiction and emotional intelligence among teenagers at SMK Informatika Sumedang. Therefore, Therefore, teenagers need to use gadgets wisely so as not to have an impact on the emotional development of adolescents.